A single antenna with wideband and narrowband functions - Alhassan, Ibrahim Bala (2014)
Wireless communication is the process of exchanging information between two or more entities over air facilitated by wireless devices. Antenna serves as the interface between the hardware and free space. To achieve high data rates and high capacity it is essential that a system capable of attaining such rates be complemented with the appropriate wideband antenna, for specific applications requiring less adjacent channel interference and also concentrated power at certain utilized/desirable frequencies requires antenna with good out of band rejection and precise resonance at the desired frequencies.In this project a CPW fed slot single antenna is proposed to be reconfigurable by implementing switches in order to operate in the wideband(1.7-6.0Ghz) mode and narrowband modes (3.5Ghz and 5.0Ghz). In particular, this antenna will find application in GSM (1800/1900), Bluetooth (2.4Ghz) and WLAN/WiMAX (2.4/3.3/3.5/5.0/5.5/5.8Ghz) bands which can all be found within the considered range of 1.7-6.0GHz.